Dietary Ethology and Adaptability of Parachanna Obscura (Gunther, 1861) Post-larvae Co-cultured with Zooplankton - Nana, Towa Algrient; Kengne, Tonssi Joseph Emmanuel; Songmo, Berlin-Léclair; Tendonkeng, Fernand; Efole, Ewoukem Thomas (European Journal of Applied Sciences, 2023)
Controlling the food preferences of fish post-larvae after resorption of the yolk sac as well as their stocking density are the determining factors for the success of fry production. In order to contribute to the production of Parachanna obscura fry, a study was carried out from May 8 to June 17, 2022 at the Application and Research Farm and at the Applied Ichthyology and Hydrobiology Laboratory of the University of Dschang-Cameroon. To this end, 180 post-larvae of P. obscura with an average weight of 1.05±0.18 g and an average total length of 4.97±0.46 cm were introduced into a zooplankton culture medium. The post-larvae were divided into three (3) treatments D1, D2 and D3 corresponding respectively to densities 0.25; 0.75 and 1.25 ind/l. Each treatment was repeated three times. Zooplankton data were collected every 7 days and fish samples for gut content analysis every 10 days. At the end of the trial, the results related to the survival and cannibalism rates did not show any significant difference between the treatments. Nevertheless, the lowest rate of cannibalism (5.33%) was recorded in the post-larvae subjected to the density of 1.25 ind/l. Analysis of the contents of the digestive tract indicates that food preferences decrease when fish stocking density is high. Thus, the post-larvae of P. obscura subjected to a low stocking density feed preferentially on copepods and ostracods (Io = 100%), although the presence of rotifers and cladocerans is noted. P. obscura post-larvae are selective in their choice of prey and size. This choice depends on environmental conditions (number of prey and predators present).